2016
DOI: 10.1523/jneurosci.2146-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Synapse Formation in Monosynaptic Sensory–Motor Connections Is Regulated by Presynaptic Rho GTPase Cdc42

Abstract: Spinal reflex circuit development requires the precise regulation of axon trajectories, synaptic specificity, and synapse formation. Of these three crucial steps, the molecular mechanisms underlying synapse formation between group Ia proprioceptive sensory neurons and motor neurons is the least understood. Here, we show that the Rho GTPase Cdc42 controls synapse formation in monosynaptic sensorymotor connections in presynaptic, but not postsynaptic, neurons. In mice lacking Cdc42 in presynaptic sensory neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…In situ hybridizations were performed according to standard protocols (Imai et al, 2016). Template DNAs were cloned into the pCRII vector (Life Technologies) by PCR using following primers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ hybridizations were performed according to standard protocols (Imai et al, 2016). Template DNAs were cloned into the pCRII vector (Life Technologies) by PCR using following primers.…”
Section: Methodsmentioning
confidence: 99%
“…Dissections of spinal cords and electrophysiological recordings have been previously described in detail (Imai et al, 2016, Fukuhara et al, 2013). Briefly, spinal cords from P5–P7 newborn pups were hemisectioned in oxygenated aCSF bath.…”
Section: Methodsmentioning
confidence: 99%
“…After Ia proprioceptive sensory afferents find their appropriate target motor neurons, the synapses mature. A recent study in mice showed that loss of Cdc42, a small GTPase, caused defects in synapse formation in monosynaptic sensory-motor connections (Imai et al, 2016b). Although Cdc42 in post-synaptic neurons has been shown to control synapse formation in other regions of the CNS, knocking out Cdc42 in motor neurons (the post-synaptic neurons in monosynaptic sensory-motor connections) did not affect sensory-motor synaptogenesis (Irie and Yamaguchi, 2002; Murakoshi et al, 2011; Kim et al, 2014; Hedrick et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, the homolog CDC42 also regulates dendritic spine formation and plasticity (Tashiro et al, 2000;Tolias et al, 2011;Hedrick et al, 2016;Martin-Vilchez et al, 2017;Murakoshi et al, 2011;Bijata et al, 2017). Recently, CDC42 was also found to be required for presynaptic development in Drosophila and mice (Imai et al, 2016;Rodal et al, 2008), indicating that its roles in presynaptic assembly are evolutionarily conserved.…”
Section: Vcsc Glia Promote Synaptogenesis Through Cdc-42 and Iqgap/pes-7mentioning
confidence: 99%